I wonder what is inside? : the role of imaginary play in young children's development of emotion regulation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Pibal, Johanna Alice (Massey University, 2008)
Imaginary play is one form of social interaction whereby young children are able to develop skills and strategies for regulating emotions. This research aimed to extend an earlier study (Galyer & Evans, 2001), and further explore the relationships between children's play, emotion regulation and social skills, within a natural setting and in a wider context. The participants were 40 preschool boys and girls who were assessed by means of the imaginary play questionnaire, Emotion Regulation Checklist, Social Skills Rating System: Preschool Form, as well as observations of imaginary play, emotion regulation, and social skills within storytelling and imaginary play activities. Children with more positive emotion regulation skills had well developed assertive and cooperative skills while their assertive, cooperative and self control skills were all related. The imaginary play activity showed children who continued pretence and who were less reliant on visual confirmation were more able to regulate their emotions. The findings add further support for the relationship between imaginary play and emotion regulation, however additional research is recommended to define the qualities of the parent's/caregiver's and children's social interaction within imaginary play and how this influences children's development of emotion regulation.
Keywords: Psychological aspects of play; Emotions in children; Control (Psychology)